Psoriasis increases the risk of Sjögren’s syndrome: evidence from a propensity score-matched cohort study and transcriptomic analysis - Zijian Kang; Yu Du; Ran Cui; Qian Wang; Miao Chen; Yu-Hsun Wang; James Cheng‐Chung Wei; Sheng-Ming Dai (BMC Medicine)
Abstract Background Despite the well-documented immune dysregulation in both psoriasis and Sjögren’s syndrome (SS), the specific link between these two autoimmune diseases has not been extensively explored. The present study aims to investigate the impact of psoriasis on the risk of SS. Methods A retrospective cohort study using TriNetX data compared SS development in patients with psoriasis and controls using propensity score matching, Kaplan–Meier curves, and Cox models. Transcriptome data were analyzed to identify shared differentially expressed genes and pathways between the two diseases. Results A total of 293,905 patients with psoriasis and an equal number of individuals without psoriasis were included. After propensity score matching, the baseline characteristics of both groups were balanced. During the follow-up period, 3339 patients with psoriasis and 1937 individuals without psoriasis developed SS. The Kaplan–Meier curves indicated a significantly higher risk of developing SS in the psoriasis group compared to the non-psoriasis group. Upon adjustment for multiple confounding factors, the risk of developing SS in the psoriasis group was 50% higher in the psoriasis group than the non-psoriasis group (hazard ratio [HR] 1.50, 95% confidence interval [CI] 1.42–1.58). Subgroup analyses confirmed the elevated risk of SS associated with psoriasis. Patients with psoriatic arthritis (PsA) and those treated with biological agents had an even higher risk of developing SS. Transcriptomic analysis revealed potential shared pathogenesis of psoriasis and SS involving cellular proliferation, immune cell recruitment, cytokine secretion, and the interferon response to viral infections. Conclusions Psoriasis might increase the risk of developing SS, which is augmented by PsA. The overlapping immunological mechanisms may underlie the co-occurrence of psoriasis and SS.